Circulating Levels of Sirtuin 4, a Potential Marker of Oxidative Metabolism, Related to Coronary Artery Disease in Obese Patients Suffering from NAFLD, with Normal or Slightly Increased Liver Enzymes. (17th June 2014) - Tarantino, Giovanni; Finelli, Carmine; Scopacasa, Franco; Pasanisi, Fabrizio; Contaldo, Franco; Capone, Domenico; Savastano, Silvia
Abstract : The present study shows low circulating levels of SIRT4 in obese patients with nonalcoholic fatty liver disease mirroring its reduced mitochondrial expression in an attempt to increase the fat oxidative capacity and then the mitochondrial function in liver and in muscle. SIRT4 modulates the metabolism of free fatty acids reducing their high circulating levels but, unfortunately, increasing ROS production. Great concentration of free fatty acids, released by adipose tissue, coupled with oxidative stress, directly results in endothelial dysfunction, early atherosclerosis, and coronary artery disease risk factor.